DIFFERENCES IN INTERLEUKIN-23 SERUM LEVELS TOWARDS THE SEVERITY OF ACNE VULGARIS IN WOMEN - Wafi Banadzir Resya; Novi Kusumaningrum; Santoso Jaeri; Astika Widy Utomo (Jurnal Kedokteran Diponegoro, 2021)
Background: Acne vulgaris is a chronic inflammatory disease in the pilosebaceous gland of the skin which can cause depression and anxiety. IL-23 is a cytokine that is involved in autoimmune diseases, including acne vulgaris. IL-23 affects the differentiation process of Th17 which further produces IL-17, an important component in the pathogenesis of acne vulgaris. IL-17 plays a significant role in the grade of skin damage caused by the inflammation process.